Projected changes in prevailing winds for transatlantic migratory birds under global warming. (31st January 2017) - La Sorte, Frank A.; Fink, Daniel
Summary: A number of terrestrial bird species that breed in North America cross the Atlantic Ocean during autumn migration when travelling to their non‐breeding grounds in the Caribbean or South America. When conducting oceanic crossings, migratory birds tend to associate with mild or supportive winds, whose speed and direction may change under global warming. The implications of these changes for transoceanic migratory bird populations have not been addressed. We used occurrence information from eBird (1950–2015) to estimate the geographical location of population centres at a daily temporal resolution across the annual cycle for 10 transatlantic migratory bird species. We used this information to estimate the location and timing of autumn migration within the transatlantic flyway. We estimated how prevailing winds are projected to change within the transatlantic flyway during this time using daily wind speed anomalies (1996–2005 and 2091–2100) from 29 Atmosphere‐Ocean General Circulation Models implemented under CMIP5. Autumn transatlantic migrants have the potential to encounter strong westerly crosswinds early in their transatlantic journey at intermediate and especially high migration altitudes, strong headwinds at low and intermediate migration altitudes within the Caribbean that increase in strength as the season progresses, and weak tailwinds at intermediate and high migration altitudes east of the Caribbean. The CMIP5 simulations suggest that, during this century, the likelihood of autumn transatlantic migrants encountering strong westerly crosswinds will diminish. As global warming progresses, the need for species to compensate or drift under the influence of strong westerly crosswinds during the initial phase of their autumn transatlantic journey may be diminished. Existing strategies that promote headwind avoidance and tailwind assistance will likely remain valid. Thus, climate change may reduce time and energy requirements and the chance of mortality or vagrancy during a specific but likely critical portion of these species' autumn migration journey. Abstract : The authors assess the implications of projected changes in prevailing winds for terrestrial birds that conduct transatlantic migration. Current projections suggest headwinds and tailwinds will remain unchanged, whereas the strength of crosswinds will decline. Thus, the need for species to compensate or drift under the influence of crosswinds will be diminished.